2020
DOI: 10.3390/su12124807
|View full text |Cite
|
Sign up to set email alerts
|

Methodology to Prioritize Climate Adaptation Measures in Urban Areas. Barcelona and Bristol Case Studies

Abstract: In the current context of fast innovation in the field of urban resilience against extreme weather events, it is becoming more challenging for decision-makers to recognize the most beneficial adaptation measures for their cities. Detailed assessment of multiple measures is resource-consuming and requires specific expertise, which is not always available. To tackle these issues, in the context of the H2020 project RESCCUE (RESilience to cope with Climate Change in Urban arEas), a methodology to effectively prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…For the case of Barcelona, the development and calibration of a 1D/2D USM and its integration in several loosely coupled (or integrated) models allowed us to perform a multi-risk analysis whose main important outputs are shown in Table 5. Moreover, the geographic detailed analysis of the potential flood impacts could help in the prioritization of the implementation of adaptation measures [46]. For example, the results provided by some impact models concerning intangible (safety for pedestrians and vehicles, stability of containers) and tangible (economic losses for properties and vehicles) damage indicate that the highest economic and social risks are concentrated in the districts located in the downtown of the city (near the sea).…”
Section: Discussionmentioning
confidence: 99%
“…For the case of Barcelona, the development and calibration of a 1D/2D USM and its integration in several loosely coupled (or integrated) models allowed us to perform a multi-risk analysis whose main important outputs are shown in Table 5. Moreover, the geographic detailed analysis of the potential flood impacts could help in the prioritization of the implementation of adaptation measures [46]. For example, the results provided by some impact models concerning intangible (safety for pedestrians and vehicles, stability of containers) and tangible (economic losses for properties and vehicles) damage indicate that the highest economic and social risks are concentrated in the districts located in the downtown of the city (near the sea).…”
Section: Discussionmentioning
confidence: 99%
“…The simulations of adaptation measures considered the implementation of Sustainable Urban Drainage Systems (SUDS), resulting in high hazard reductions. Further implementation of structural measures could practically eliminate high flood hazard conditions for people and assets for low return periods (up to 10 years) [20].…”
Section: Hazard Assessment Summary For the Three Citiesmentioning
confidence: 99%
“…For the case of Bristol, hazard assessment indicated that climate change could significantly increase hazard produced by tidal, river and pluvial floods. Bristol adaptation strategies to face pluvial flooding problem considered the implementation of different local adaptation measures (SUDS, increase of pipe and pumping capacity) to solve the most important problems in flood prone areas identified by simulations of Baseline and BAU scenarios [14,20]. For tidal and river flooding, adaptation measures limiting people and assets exposure were selected so no hazard assessment was performed in this case.…”
Section: Hazard Assessment Summary For the Three Citiesmentioning
confidence: 99%
See 1 more Smart Citation
“…City resilience reflects the overall capacity of a city (individuals, communities, institutions, businesses and systems) to survive, adapt and thrive no matter what kinds of chronic stresses or acute shocks they experience [1]. This capacity may be acquired through adopting structural and non-structural solutions and/or introducing knowledge and intelligence in the management of city infrastructures [2].…”
Section: Introductionmentioning
confidence: 99%